2021
DOI: 10.3390/jpm11100984
|View full text |Cite
|
Sign up to set email alerts
|

Insulin as Monotherapy and in Combination with Other Glucose-Lowering Drugs Is Related to Increased Risk of Diagnosis of Pneumonia: A Longitudinal Assessment over Two Years

Abstract: Objective: Patients with type 2 diabetes mellitus (T2DM) are at an increased risk of developing infectious diseases such as pneumonia. Hitherto, there has been uncertainty as to whether there is a relationship between different antidiabetic drug combinations and development of pneumonia in this specific cohort. Research Design and Methods: In this longitudinal retrospective study we used multiple logistic regression analysis to assess the odds ratios (ORs) of pneumonia during an observational period of 2 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…The higher frequency of influenza shots in the DM population could result from more frequent visits to the general practitioner. Current literature shows that individuals with DM have a higher incidence for influenza and pneumonia and further are at higher risk for influenza-mediated and pneumonia-related morbidity and mortality [ 10 , 15 ]. Due to the higher influenza-related morbidity and mortality in individuals with diabetes mellitus the general practitioner could be more likely to suggest the annual flu shot to DM individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher frequency of influenza shots in the DM population could result from more frequent visits to the general practitioner. Current literature shows that individuals with DM have a higher incidence for influenza and pneumonia and further are at higher risk for influenza-mediated and pneumonia-related morbidity and mortality [ 10 , 15 ]. Due to the higher influenza-related morbidity and mortality in individuals with diabetes mellitus the general practitioner could be more likely to suggest the annual flu shot to DM individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, diabetes mellitus can alter the immune system and therefore increase the risk of infections. For example, an Austrian study investigated higher risk for pneumonia in a cohort with diabetes mellitus [ 10 ]. In particular the high blood glucose levels in DM individuals alters the immune system and impairs the immune response [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glucose-lowering drugs lower blood sugar by restoring the insulin inhibition of adenylyl cyclase, inhibiting the intestinal absorption of glucose, reducing hepatic glucose output, improving insulin sensitivity, increasing glucose uptake and utilization by peripheral tissues, muscle and fat, and promoting anaerobic glycolysis. Recent clinical and animal research has confirmed that combination therapy with glucose-lowering drugs can effectively modify insulin resistance, oxidative stress and inflammatory response for the effective treatment of diabetes and its complications [ 170 , 171 , 172 ]. Therefore, the loading of hypoglycemic agents into fiber dressings for diabetic trauma therapy by electrospinning technology is of great significance.…”
Section: Electrospinning Nanofiber In Diabetic Wound Therapymentioning
confidence: 99%
“…Previously, we reported that insulin users, compared with nonusers, experienced 2.5-fold increased hazard of all-cause mortality during a mean 7.8 years in a nationwide cohort with recently-diagnosed T2DM [ 12 ]. Leutner et al [ 13 ] also reported that stable monotherapy with insulin and insulin in combination with other antidiabetic medications were associated with increased risk of pneumonia in people with T2DM compared to untreated controls.…”
Section: Introductionmentioning
confidence: 99%